Given:
M=(x1, y1)=(-2,-1),
N=(x2, y2)=(3,1),
M'=(x3, y3)= (0,2),
N'=(x4, y4)=(5, 4).
We can prove MN and M'N' have the same length by proving that the points form the vertices of a parallelogram.
For a parallelogram, opposite sides are equal
If we prove that the quadrilateral MNN'M' forms a parallellogram, then MN and M'N' will be the oppposite sides. So, we can prove that MN=M'N'.
To prove MNN'M' is a parallelogram, we have to first prove that two pairs of opposite sides are parallel,
Slope of MN= Slope of M'N'.
Slope of MM'=NN'.
![\begin{gathered} \text{Slope of MN=}\frac{y2-y1}{x2-x1} \\ =\frac{1-(-1)}{3-(-2)} \\ =\frac{2}{5} \\ \text{Slope of M'N'=}\frac{y4-y3}{x4-x3} \\ =\frac{4-2}{5-0} \\ =\frac{2}{5} \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20%5Ctext%7BSlope%20of%20MN%3D%7D%5Cfrac%7By2-y1%7D%7Bx2-x1%7D%20%5C%5C%20%3D%5Cfrac%7B1-%28-1%29%7D%7B3-%28-2%29%7D%20%5C%5C%20%3D%5Cfrac%7B2%7D%7B5%7D%20%5C%5C%20%5Ctext%7BSlope%20of%20M%27N%27%3D%7D%5Cfrac%7By4-y3%7D%7Bx4-x3%7D%20%5C%5C%20%3D%5Cfrac%7B4-2%7D%7B5-0%7D%20%5C%5C%20%3D%5Cfrac%7B2%7D%7B5%7D%20%5Cend%7Bgathered%7D)
Hence, slope of MN=Slope of M'N' and therefore, MN parallel to M'N'
![\begin{gathered} \text{Slope of MM'=}\frac{y3-y1}{x3-x1} \\ =\frac{4-(-1)}{5-(-2)} \\ =\frac{3}{2} \\ \text{Slope of NN'=}\frac{y4-y2}{x4-x2} \\ =\frac{4-1}{5-3} \\ =\frac{3}{2} \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20%5Ctext%7BSlope%20of%20MM%27%3D%7D%5Cfrac%7By3-y1%7D%7Bx3-x1%7D%20%5C%5C%20%3D%5Cfrac%7B4-%28-1%29%7D%7B5-%28-2%29%7D%20%5C%5C%20%3D%5Cfrac%7B3%7D%7B2%7D%20%5C%5C%20%5Ctext%7BSlope%20of%20NN%27%3D%7D%5Cfrac%7By4-y2%7D%7Bx4-x2%7D%20%5C%5C%20%3D%5Cfrac%7B4-1%7D%7B5-3%7D%20%5C%5C%20%3D%5Cfrac%7B3%7D%7B2%7D%20%5Cend%7Bgathered%7D)
Hence, slope of MM'=Slope of NN' nd therefore, MM' parallel to NN'.
Since both pairs of opposite sides of MNN'M' are parallel, MM'N'N is a parallelogram.
Since the opposite sides are of equal length in a parallelogram, it is proved that segments MN and M'N' have the same length.
Answer:
yes I can help
Step-by-step explanation:
which one please
Answer: p=8h
Hope this helped
Step-by-step explanation:
Step-by-step explanation:
Volume = l * b * h
![volume \: = 5 \times 6 \times 8 \\ = 240 \: cm^{3}](https://tex.z-dn.net/?f=volume%20%5C%3A%20%20%3D%205%20%5Ctimes%206%20%5Ctimes%208%20%5C%5C%20%20%3D%20240%20%5C%3A%20cm%5E%7B3%7D%20)